Notes relating to 'A.Z.,' The Anonymous correspondent of the Society, by whom the collection of Books and Mss. relating to the Orkney and Shetland Islands, were presented to the Library (see Archaeologia Scotica, vol. iii., p.267.) (Proceedings of the Society of Antiquaries of Scotland, 1854)
W. H. Fotheringhame speculates on the identity of an anonymous correspondent (A. Z.) who provided manuscripts relating to Orkney and Shetland to the Society's library, as listed in the Archaeologia Scotica. He suggests that A. Z. was John Munro, a clerk from Kirkwall. Fortheringhame lists his evidence, including handwriting comparisons and a personal anecdote found in the notes to one of his volumes alluding to A. Z.'s early life in a tenement in Kirkwall. Unfortunately, John Munro's sister had all his papers destroyed when she died, but Fotheringhame concludes that the evidence in this article should be enough to prove that A. Z. was John Munro.